Does Depth Matter? Reproduction Pattern Plasticity in Two Common Sponge Species Found in Both Mesophotic and Shallow Waters - Idan, Tal; Goren, Liron; Shefer, Sigal; Brickner, Itzchak; Ilan, Micha (Frontiers in Marine Science, 2020)
Determining demosponge reproductive strategies is essential to understanding their ecology and life history, as well as for the management of benthic marine environments. This is especially important in mesophotic ecosystems, which have been suggested to serve as a refuge for shallow-water populations and for which knowledge is lacking. Here we compared the reproductive strategies of two common Mediterranean demosponges species: Chondrosia reniformis and Axinella polypoides, which can be found in both shallow and mesophotic habitats along the Israeli coast. Samples were collected over two years, via SCUBA diving from the shallow coast (2-32 m) and Remotely Operated Vehicle from the mesophotic sponge grounds (95-120 m). A. polypoides and C. renifornis differed in oocyte morphology and development, but both demonstrated reproductive plasticity with regard to temperature and depth: temperature appears to regulate their reproduction in the shallow water, as both species exhibited seasonality; whereas, in the mesophotic zone, where the temperature amplitude is much smaller, seasonality was not observed for either species. Furthermore, in the mesophotic zone, C. reniformis exhibited low fecundity and probably invests more in asexual reproduction by budding. Mesophotic A. polypoides, in contrast, exhibited enhanced and continuous asynchronous sexual reproduction year-round. Our findings suggest that reproduction plasticity may be a general rule for sponge species that inhabit different habitats; such plasticity could allow sponges to thrive in different environmental conditions. These findings further emphasize the importance of protecting the mesophotic sponge grounds, which can serve as a refuge in the face of the adverse impact of anthropogenic disturbances and rising seawater temperatures.